Pendampingan Pembuatan Izin Legalitas Usaha (SP-PIRT) Produksi Cistik Sofia di Dusun Kalitengah, Magelang - Hary Abdul Hakim; Chrisna Bagus Edhita Praja; Suharso Suharso; Diana Setiawati; Putri Dwi Arianti; Dian Novitasari; Ahmad Agung Febrianto; Rakhmat Dian Hidayat; Panji Nagaro (Borobudur Journal on Legal Services, 2022)
The community service program aims to assist in making the legality of business licenses with the Home Industry Food Production Certificate (SPP-IRT) for Cistik Sofia processed. For most of the people in Kalitengah Hamlet, Glagahombo Village, Tegalrejo District, Magelang Regency, currently many are starting to develop businesses in the field of processed snack products in the form of Cheesse Sticks. The processed food is used as an alternative business in improving the welfare of the residents. The program is carried out through assistance in the process of filing business legality stages. As for the implementation of this program, several stages of the SP-PIRT submission process have been carried out including filling out the application form, product laboratory testing, and sanitation testing.